Tackling Public Service Delivery Challenges Through Appropriate Work Ethics in Nigeria - Mojisola E. Akinlade; Daniel E. Gberevbie; Ugochukwu D. Abasilim (PERSPEKTIF, 2022)
This study focuses not only on identifying the ethical challenges hindering public service delivery but to state how these challenges can be tackled to bring out the desired service delivery demanded by the citizens. Also, this studyproffer suggestions on the work ethics mechanisms that can be employed to enhance the service delivery. The Ekiti State University Teaching Hospital (EKSUTH), Ado-Ekiti, Nigeria was used as the study area and it adopted the cross-sectional survey research design. The primary source of data was obtained from the administration of questionnaires to both EKSUTH staff (administrative and clinical departments) and EKSUTH out-patients followed by an in-depth interview with four administrative and four clinical staff. The Pearson Product Moment Correlation, Linear Regression Analysis, and One Sample T-test Analysis were used to test the various hypotheses, and the study findings reveals that there is a link between work ethics and service delivery, also, a proper implementation of standard work ethics can lead to increased efficiency in the public sector. Based on these observations, the researcher suggests that EKSUTH Management should bring up strategical ways in improving the work ethics that would bring about the desired public service delivery.